PERANCANGAN SISTEM KEAMANAN KENDARAAN RODA DUA MENGGUNAKAN RFID DIPROGRAM - Gulo, Sardiman; Hutabarat, Marvin F. S.; Pangaribuan, Melva (LPPM ISTP, 2024)
ABSTRACT To improve motorcycle security when parked so that it is not easily stolen by thieves, a two-wheeled vehicle security system is designed using RFID and programmed buzzers. The tool is designed to use an Arduino Uno module, an RFID reader module, a relay module, an RFID card and a key chain. The Arduino Uno module functions as a CPU, the RFID reader functions to read RFID contents in the form of a card and in the form of a keychain, the relay module functions as a breaker and connector for electric current. Testing of two-wheeled vehicle security system tools using RFID and programmed buzzers has been carried out. The test results show that the contents of the RFID code can be read, both in the form of cards and key chains. RFID, whose code can be read, is entered into a program that is uploaded to Arduino Uno's flash memory. RFID in the form of a card and key chain which has been entered into the contents of the code into the program which is uploaded to Arduino Uno can turn off the machine and activate the buzzer, turn on and turn off the buzzer.